Negative pole piece, preparation method thereof, cylindrical battery and electronic cigarette
By using pure silicon particles with high capacity as the negative electrode material and optimizing the design of the negative electrode sheet, the problem of insufficient energy density and rate performance of existing electronic cigarette lithium-ion batteries is solved, and higher energy density and rate performance is achieved. Meets market demand.
Patent Information
- Application Number
- CN202510040934.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The energy density and rate performance of existing electronic cigarette lithium-ion batteries are limited by electrode materials and electrode sheet design, especially the negative electrode material has a low gauge capacity and cannot meet the needs of higher energy density.
Pure silicon particles are used as the negative electrode material, and by controlling the coating layer thickness of the negative electrode sheet, the negative electrode sheet is thinned, shortening the migration distance between electrons and ions, reducing the internal resistance of the battery, and improving the rate performance.
It significantly improves the energy density and rate performance of the battery, meets the market's demand for high-efficiency, high-capacity, safe and reliable battery products, and has broad market application prospects.
Smart Images

Figure CN119480912A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode plate, a preparation method thereof, a cylindrical battery, and an electronic cigarette. Background Art
[0002] Lithium-ion batteries have become an ideal power source for portable electronic devices such as e-cigarettes due to their high energy density, long cycle life, and small volume-to-weight ratio. In recent years, with the continuous development of the e-cigarette market, consumers' expectations for e-cigarettes have also been continuously upgraded. They not only pursue long-lasting battery life, but also desire a delicate and rich taste experience. In this context, high-energy-density and high-rate lithium-ion batteries, as the core element to enhance the overall experience of e-cigarettes, have continued to rise in market demand and have become the main driving force for the development of the e-cigarette industry.
[0003] The high energy density state of the electronic cigarette lithium-ion battery is one of the important factors that determine its service life. Batteries with high energy density can provide more electrical energy at the same volume and weight, thereby extending the use time of electronic cigarettes. The high rate performance of electronic cigarette lithium-ion batteries is an important factor influencing the user experience of electronic cigarettes. High-rate electronic cigarette lithium-ion batteries can provide higher discharge currents, thereby supporting the efficient operation of electronic cigarette atomizers, producing more smoke and better taste. However, the energy density and rate performance of lithium-ion batteries are affected by multiple factors, including electrode materials, battery cell pole piece design, and manufacturing processes. Therefore, in order to pursue high energy density and high-rate electronic cigarette lithium-ion batteries, manufacturers are constantly exploring new battery materials and manufacturing processes to promote the continuous updating and iteration of electronic cigarette products.
[0004] For example, the Chinese patent application authorization number CN111342005B discloses a method for preparing an electronic cigarette lithium-ion battery, wherein the positive electrode uses high-voltage and high-compacted lithium cobalt oxide, and the lithium cobalt oxide is coated with an antioxidant, and the negative electrode uses silicon-carbon material, and is matched with an optimized electrolyte formula, so as to realize the preparation of a high-voltage, high-energy-density, and high-rate electronic cigarette lithium-ion battery. However, this method uses a composite material of silicon-carbon and graphite as the negative electrode active material, and the maximum gram capacity of the negative electrode material is only about 500mAh / g, which cannot achieve a higher energy density. Another example is a method for preparing an ultra-large diameter cylindrical electronic cigarette battery disclosed in the Chinese patent application publication number CN118738292A, wherein the positive electrode uses lithium cobalt oxide and a rate-type ternary composite material with high rate performance, and is matched with graphite as the negative electrode, and the capacity of the battery is increased by adjusting the positive electrode ratio, surface density, and compaction density; at the same time, a conductive agent with high conductivity is selected to increase the proportion of the active main material, thereby achieving the purpose of increasing the battery volume energy density and rate performance. However, its negative electrode uses a graphite negative electrode with a theoretical capacity of only 374mAh / g, which limits the energy density of the battery.
[0005] Therefore, how to effectively improve the energy density and rate performance of electronic cigarette lithium-ion batteries requires comprehensive consideration of electrode materials and pole piece design. Silicon materials have been applied in negative electrode materials with a theoretical capacity of 4200mAh / g, such as silicon-based, silicon-based, silicon-carbon and other high-gram capacity materials, but a large amount of carbon addition loses the high capacity of silicon and cannot meet the demand for higher energy density. Summary of the invention
[0006] The purpose of the present invention is to provide a negative electrode plate, a preparation method thereof, a cylindrical battery, and an electronic cigarette. The negative electrode plate of the present invention uses pure silicon particles as the negative electrode material, has an extremely high gram capacity, and can significantly improve the energy density of the battery. At the same time, by controlling the thickness of the coating layer of the negative electrode plate, a thin design of the negative electrode plate is achieved, so that the migration distance of electrons and ions is shortened, which is beneficial to reducing the internal resistance of the battery and improving the rate performance of the battery.
[0007] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a negative electrode sheet, comprising a negative electrode current collector, a negative electrode tab disposed on the negative electrode current collector, and a negative electrode silicon-based active material; The negative electrode silicon-based active material comprises pure silicon particles, and the mass percentage of the pure silicon particles in the negative electrode silicon-based active material is 65-100%; The negative electrode silicon-based active material forms a first coating surface and a second coating surface on the upper and lower surfaces of the negative electrode current collector, respectively, and the sum of the thickness of the first coating surface and the second coating surface is 12 μm-20 μm; In one embodiment, the gram capacity of the pure silicon particles is ≥3200 mAh / g.
[0008] In one embodiment, the average particle size of the pure silicon particles is 3.0-6.0 μm.
[0009] In one embodiment, the double-sided surface density of the negative electrode plate is 1.6-2.4 mg / cm 2 .
[0010] In one embodiment, the compaction density of the negative electrode sheet is 1.1-1.3 g / cm 3 .
[0011] In one embodiment, the thickness of the negative electrode plate is 18 μm-28 μm.
[0012] In one embodiment, the first coated surface and the second coated surface respectively include two negative electrode coating areas, and the negative electrode tab is welded in a first blank area between the two negative electrode coating areas of the first coated surface, or the negative electrode tab is welded in a second blank area between the two negative electrode coating areas of the second coated surface.
[0013] In one embodiment, the distance between the two coating areas is 2-8 times the width of the negative electrode tab.
[0014] In one embodiment, the welding area between the negative electrode tab and the negative electrode sheet is greater than 8 mm 2 .
[0015] The beneficial effect of the negative electrode sheet provided by the present invention is that by selecting high-gram capacity and easy-to-produce micron silicon particles as the negative electrode main material, not only can the production cost of the negative electrode main material be effectively reduced, but also the demand for high volume energy density can be achieved. At the same time, by controlling the surface density and compaction density of the negative electrode sheet to regulate the thickness of the micron silicon particles on the negative electrode current collector, the thickness of the coating layer of the negative electrode sheet is reduced while ensuring the lithium storage capacity of the negative electrode sheet, and the migration distance of lithium ions during the charge and discharge process is reduced, which is conducive to improving the migration resistance of lithium ions during the charge and discharge process, reducing the internal resistance of the negative electrode sheet, achieving the purpose of increasing the current, and improving the conductivity of the negative electrode sheet.
[0016] In a second aspect, the present invention further provides a method for preparing the above-mentioned negative electrode sheet, comprising the following steps: A: The pure silicon particle material, the conductive agent and the binder are uniformly dispersed in a solvent to obtain a negative electrode coating slurry, wherein the solid content of the negative electrode slurry is 10-15wt%, and the viscosity of the negative electrode slurry is 4000-15000mPa.s -1 ; B: The negative electrode coating slurry is coated on the surface of the current collector, and the negative electrode sheet is obtained after drying and rolling.
[0017] The beneficial effect of the preparation method of the negative electrode plate provided by the present invention is that the present invention increases the total specific surface area of all particles in the slurry by using various conductive agents with higher specific surface areas, and matches them with a binder system with better thickening effect, while optimizing a better mixing order, thereby ensuring the fluidity and stability of the slurry, so that the negative electrode can also ensure the uniformity and consistency of the coating when the coating is thin, avoiding scratches and uneven thickness.
[0018] In a third aspect, the present invention further provides a cylindrical battery, comprising an aluminum-plastic shell, an electrolyte placed in the shell, and a cylindrical winding core, wherein the cylindrical winding core comprises a positive electrode sheet, a separator, and the above-mentioned negative electrode sheet.
[0019] In one of the embodiments, the positive electrode plate includes a positive electrode current collector, a positive electrode tab disposed on the positive electrode current collector, and a positive electrode active material, and the positive electrode active material is one of lithium manganese oxide or lithium cobalt oxide.
[0020] In one embodiment, the positive electrode active material is lithium cobalt oxide, and the proportion of lithium cobalt oxide in the positive electrode active material is 80-100wt%.
[0021] In one embodiment, the average particle size of the lithium cobalt oxide is 4.5-6.0 μm.
[0022] In one of the embodiments, it is characterized in that the positive electrode active material forms a third coating surface and a fourth coating surface on the upper and lower surfaces of the positive electrode current collector, respectively; the third coating surface and the fourth coating surface respectively include two positive electrode coating areas, and the positive electrode tab is welded in a third blank area between the two positive electrode coating areas of the third coating surface, or the positive electrode tab is welded in a fourth blank area between the two positive electrode coating areas of the fourth coating surface.
[0023] In one embodiment, the length of the positive electrode plate is 745-750mm, and the width is 20-25mm; the length of the negative electrode plate is 800-805mm, and the width is 20-25mm; the cylindrical battery has a battery capacity of 580-700mAh at a discharge rate of 0.2C.
[0024] In one embodiment, the length of the positive electrode plate is 745-750mm, and the width is 25-30mm; the length of the negative electrode plate is 800-805mm, and the width is 25-30mm; the cylindrical battery has a battery capacity of 710-810mAh at a discharge rate of 0.2C.
[0025] In one embodiment, the length of the positive electrode plate is 745-750 mm, and the width is 30-35 mm; the length of the negative electrode plate is 800-805 mm, and the width is 30-35 mm; the cylindrical battery has a battery capacity of 820-920 mAh at a discharge rate of 0.2C.
[0026] In one embodiment, the length of the positive electrode plate is 1300-1320 mm, and the width is 25-35 mm; the length of the negative electrode plate is 1360-1380 mm, and the width is 25-35 mm; the cylindrical battery has a battery capacity of 1000-1600 mAh at a discharge rate of 0.2C.
[0027] In one embodiment, the length of the positive electrode plate is 1300-1320 mm, and the width is 40-45 mm; the length of the negative electrode plate is 1360-1380 mm, and the width is 40-45 mm; the cylindrical battery has a battery capacity of 2100-2400 mAh at a discharge rate of 0.2C.
[0028] In one embodiment, the length of the positive electrode plate is 1300-1320 mm, and the width is 50-55 mm; the length of the negative electrode plate is 1360-1380 mm, and the width is 50-55 mm; the cylindrical battery has a battery capacity of 2500-2900 mAh at a discharge rate of 0.2C.
[0029] The beneficial effects of a cylindrical battery provided by the present invention are: by adopting the above-mentioned negative electrode pole piece and using pure silicon particles as the negative electrode material, the high capacity characteristics of the silicon material are fully utilized, the capacity of the battery is significantly improved, and by optimizing the manufacturing process of the pole piece, the high-rate discharge characteristics of the battery are achieved at the same time, the comprehensive performance of the cylindrical battery is improved, and the market's urgent demand for high-efficiency, high-capacity, safe and reliable battery products is met, and it has broad market application prospects and social value; the use of the above-mentioned negative electrode pole piece can meet the design requirements of cylindrical batteries of different sizes, and can be customized according to the needs of different electronic devices. It is widely used in portable electronic devices, electric vehicles, energy storage systems and other fields, showing wide applicability and market competitiveness.
[0030] In a fourth aspect, the present invention further provides an electronic cigarette, comprising the above-mentioned cylindrical battery.
[0031] The beneficial effect of the electronic cigarette provided by the present invention is that by adopting the above cylindrical battery, a longer battery life can be provided for the electronic cigarette, the user's demand for high performance and long standby time can be met, and the user's use experience can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic structural diagram of a first coating surface of a negative electrode current collector of a negative electrode plate provided by the present invention; Figure 2 A schematic structural diagram of a second coating surface of a negative electrode current collector of a negative electrode plate provided by the present invention; Figure 3 A side view of a negative electrode current collector of a negative electrode plate provided by the present invention; Figure 4 A schematic structural diagram of a third coating surface of a positive electrode current collector of a positive electrode plate provided by the present invention; Figure 5 A schematic structural diagram of a fourth coating surface of a positive electrode current collector of a positive electrode plate provided by the present invention; Figure 6 A side view of a positive electrode current collector of a positive electrode plate provided by the present invention; Figure 7 A schematic structural diagram of a cylindrical battery provided by the present invention; Description of reference numerals: 100, cylindrical battery; 10, negative electrode; 20, positive electrode; 30, diaphragm; 40, aluminum-plastic shell; 11. Negative electrode current collector; 111, first coating surface; 111A, first coating area; 111B, second coating area; 111C, first blank area; 112, second coating surface; 112A, third coating area; 112B, fourth coating area; 112C, second blank area; 113. first side edge; 114. second side edge; 12, negative electrode tab; 121, first conductive sheet; 121A, first ultrasonic weld; 122, first insulating sheet; 123, second insulating sheet; 21. Positive electrode current collector; 211, third coating surface; 211A, fifth coating area; 211B, sixth coating area; 211C, third blank area; 212, fourth coating surface; 212A, seventh coating area; 212B, eighth coating area; 212C, fourth blank area; 213, third side; 214, fourth side; 22, positive electrode tab; 221, second conductive sheet; 221A, second ultrasonic weld mark; 222, third insulating sheet; 223, fourth insulating sheet. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0035] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way is inclusive and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range.
[0036] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0037] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0038] If not specifically stated, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially.
[0039] As the demand for lithium-ion battery energy density becomes higher and higher, and the charging time requirement becomes shorter and shorter, the theoretical capacity of 374mAh / g of graphite negative electrode gradually limits the development of batteries in the field of high energy density. Silicon negative electrode with high theoretical capacity is regarded as the most promising negative electrode material for high specific energy lithium-ion battery. Compared with nano silicon, micron silicon has lower raw material cost, higher tap density and smaller surface area, and has advantages in improving volume energy density and limiting interface side reactions. Therefore, the inventors of this application selected micron pure silicon with high gram capacity as the negative electrode active material, and controlled the surface density and compaction density of the negative electrode plate 10 to achieve the regulation of the thickness of the negative electrode plate 10, so as to reduce the thickness of the negative electrode plate 10 as much as possible, reduce the migration distance of lithium ions during charging and discharging, improve the migration resistance of lithium ions during charging and discharging, and improve the conductivity of the negative electrode plate 10, so as to achieve the improvement of energy density and rate performance of lithium-ion batteries.
[0040] like Figure 1-3 As shown, it is a schematic diagram of the structure of a negative electrode sheet 10 provided by the present invention. In the present invention, the length direction of the negative electrode sheet 10 itself is defined as X, the width direction is defined as Y, and the thickness direction is defined as Z. It should be understood that the above definition of the direction is for the purpose of convenient description of the present invention, and the direction defined in the present invention can be understood according to the relative position of the attached figure and the actual product. It can be understood that the length direction, width direction and thickness direction of the negative electrode current collector 11 and the negative electrode silicon-based active material itself are the same as those of the negative electrode sheet 10. Figure 1 and Figure 2 The negative electrode sheet 10 in one embodiment of the present invention is shown along its length direction X. Figure 3The figure shows the negative electrode sheet 10 along its thickness direction Z in one embodiment of the present invention.
[0041] like Figure 1-3 As shown, the negative electrode plate 10 provided by the present invention includes a negative electrode current collector 11, a negative electrode tab 12 arranged on the negative electrode current collector 11, and a negative electrode silicon-based active material. The negative electrode current collector 11 includes a first coating surface 111 and a second coating surface 112 arranged along its thickness direction Z. The negative electrode silicon-based active material provided by the present invention is arranged on both the first coating surface 111 and the second coating surface 112 of the negative electrode current collector 11.
[0042] Among them, Figure 1 and Figure 3 As shown, the negative electrode silicon-based active material forms a first coating surface 111 on the upper surface of the negative electrode current collector 11, and a first coating area 111A and a second coating area 111B are provided on the first coating surface 111, and the lengths of the first coating area 111A and the second coating area 111B are the same. The thickness of the first coating area 111A is the thickness of the active material formed after the negative electrode silicon-based active material is coated on the upper surface of the negative electrode current collector 11 and rolled. A first blank area 111C is also provided between the first coating area 111A and the second coating area 111B, and there is no negative electrode silicon-based active material in the first blank area 111C, and the first blank area 111C is used for welding the negative electrode tab 12. A first side edge 113 is also provided on the first coating surface 111, and there is no negative electrode silicon-based active material in the first side edge 113. The first blank area 111C and the first side edge 113 without negative electrode silicon-based active material are the surface of the negative electrode current collector 11 itself.
[0043] like Figure 2-3 As shown, the negative electrode silicon-based active material forms a second coating surface 112 on the lower surface of the negative electrode current collector 11, and a third coating area 112A and a fourth coating area 112B are provided on the second coating surface 112, and the lengths of the third coating area 112A and the fourth coating area 112B are the same. The thickness of the second coating surface 112 is the thickness of the active material formed after the negative electrode silicon-based active material is coated and rolled on the lower surface of the negative electrode current collector 11. A second blank area 112C is also provided between the third coating area 112A and the fourth coating area 112B, and there is no negative electrode silicon-based active material in the second blank area 112C. The second blank area 112C is the back of the first blank area 111C to which the negative electrode tab 12 is welded. A second side edge 114 is also provided on the second coating surface 112 . No negative electrode silicon-based active material is present in the second side edge 114 . The second blank area 112C without negative electrode silicon-based active material and the second side edge 114 are the surfaces of the negative electrode current collector 11 itself.
[0044] In order to better control the stability of the negative silicon-based active material on the negative current collector 11 during battery operation and improve the conductivity of the negative silicon-based active material, the thickness of the first coating surface 111 of the negative electrode plate 10 in the present invention is 6μm-10μm; the thickness of the second coating surface 112 is 6μm-10μm. The sum of the thickness of the first coating surface 111 and the second coating surface 112 on the negative electrode plate 10 is controlled between 12μm-20μm, so that the thickness of the negative electrode plate 10 is much smaller than the thickness of the traditional negative electrode plate. The thickness of the negative silicon-based active material of the negative electrode plate 10 provided by the present invention on the first coating surface 111 and the second coating surface 112 of the negative current collector 11 can be the same or different, that is, the thickness of the first coating surface 111 and the thickness of the second coating surface 112 can be the same, or the thickness of the first coating surface 111 is greater than the thickness of the second coating surface 112, or the thickness of the first coating surface 111 is less than the thickness of the second coating surface 112. The thickness of the negative electrode silicon-based active material on the first coating surface 111 or the thickness of the negative electrode silicon-based active material on the second coating surface 112 can be adjusted separately as needed. To separately adjust the thickness of the negative electrode silicon-based active material on the two surfaces, the sum of the thicknesses of the two coating surfaces needs to be controlled between 12 μm and 20 μm. The present invention can effectively shorten the transmission distance of electrons and lithium ions inside the electrode piece by controlling the sum of the thicknesses of the first coating surface 111 and the second coating surface 112 of the negative electrode plate 10 between 12 μm and 20 μm, which helps to reduce the internal resistance of the battery and improve the rate performance of the battery.
[0045] The negative electrode silicon-based active material used in the negative electrode plate 10 provided by the present invention includes pure silicon particles, and the mass percentage of pure silicon in the negative electrode silicon-based active material is 65-100%, for example, the mass percentage of pure silicon in the negative electrode silicon-based active material is 65%, 75%, 85%, 95%, 100%, or any value between any two of the above numerical ranges. However, it is worth noting that 100% pure silicon is only discussed as a theoretical limit value. In practical applications, since it is difficult for pure silicon to reach a completely impurity-free state in its natural state, the so-called "100% pure silicon" does not actually exist. Even after a highly refined process, the silicon material will still contain trace impurity elements such as iron, aluminum, calcium, etc. The negative electrode silicon-based active material provided by the present invention can be pure silicon, or it can be pure silicon and graphite, or pure silicon and silicon-carbon material, or silicon composite material.
[0046] When the negative electrode silicon-based active material is pure silicon and graphite or pure silicon and silicon-carbon material or silicon composite material, the mass percentage of pure silicon in the negative electrode silicon-based active material is controlled at 65-100%. The present invention selects a negative electrode active material containing pure silicon particles, and the pure silicon particles have a very high theoretical specific capacity (up to 4200mAh / g), which far exceeds the theoretical specific capacity of traditional graphite negative electrodes (372mAh / g). Therefore, the use of negative electrode active materials containing pure silicon particles can significantly improve the energy density of the battery, so that the battery can store more electrical energy at the same weight or volume. In addition, compared with other high-performance negative electrode materials, the cost of pure silicon particles is relatively low, which makes it have potential cost advantages in large-scale commercial applications.
[0047] In one embodiment, the gram capacity of pure silicon particles in the negative electrode active material provided by the present invention is ≥3200mAh / g. The negative electrode silicon-based active material is the main body of lithium storage in the battery, and realizes the embedding and de-embedding of lithium ions during the charging and discharging process. The different selection of negative electrode silicon-based active materials will directly affect the lithium storage capacity of the entire lithium-ion battery, that is, the capacity of the single cell. The present invention selects pure silicon particles with high gram capacity as the key component of the negative electrode active material to ensure the energy density of the negative electrode silicon-based active material.
[0048] In one embodiment, the average particle size of the pure silicon particles in the negative electrode active material provided by the present invention is 3.0-6.0 μm. Such as 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, preferably any value between any two of the above numerical ranges. The present invention optimizes the particle size of the pure silicon particles so that the particle size of the pure silicon particles is within the range of 3.0-6.0 μm, which helps to shorten the diffusion path of lithium ions inside the pure silicon particles, thereby improving the charge and discharge rate of the battery. In addition, pure silicon particles with a smaller particle size can provide more contact points between particles, which helps to disperse the stress caused by volume changes and improve the stability of the battery.
[0049] In one embodiment, the double-sided surface density of the negative electrode plate 10 is 1.6-2.4 mg / cm 2 For example, the surface density of the two coated surfaces of the negative electrode plate 10 is 1.6 mg / cm 2 、1.8mg / cm 2 , 2.0mg / cm 2 , 2.2mg / cm 2 , 2.4mg / cm 2Or any value between any two of the above numerical ranges. The surface density values in the present invention are rounded off to one decimal place when designed and recorded, but in actual production, slight fluctuations in the surface density values must still be considered and ensured to be within a controllable range. By optimizing the double-sided surface density of the negative electrode sheet 10, the present application can achieve control over the thickness of the negative electrode sheet 10, improve the utilization rate of the negative electrode material, and thus increase the capacity and energy density of the battery.
[0050] The double-sided surface density of the negative electrode plate 10 mentioned in the present invention refers to the mass of the negative electrode active material per unit area, wherein the negative electrode active material is coated on both the upper and lower surfaces of the negative electrode plate 10. The method for measuring the unit surface density of the negative electrode plate 10 is as follows: Step 1. Use a sampler to take a circular foil of a preset area on an empty foil and weigh it to obtain the weight of the foil; Step 2. Use a sampler to take a circular electrode of the same size on the double-sided coated electrode plate and weigh it, and subtract the foil weight in step 1 and divide it by the circular area to obtain the unit surface density; Steps 1-2 can be repeated to obtain the actual surface density at different positions of the negative electrode plate 10 and then take the average value.
[0051] When the surface density of both sides of the negative electrode sheet 10 is greater than 2.4 mg / cm 2 When the double-sided surface density of the negative electrode sheet 10 is less than 1.6 mg / cm, it means that more negative electrode active materials are loaded on the same area, which may theoretically increase the capacity of the battery. However, too high a surface density will increase the thickness of the negative electrode sheet 10, resulting in an increase in the internal resistance of the battery, affecting the charge and discharge efficiency of the battery, thereby limiting the improvement of the battery capacity to a certain extent. 2 Having less active material in the coating means that the number of lithium ions that can be stored and released during the charge and discharge process decreases, and the energy that can be stored per unit volume also decreases, so the battery capacity will also decrease.
[0052] In one embodiment, the compaction density of the negative electrode sheet 10 is 1.10-1.30 g / cm 3 For example, the compaction density of the negative electrode sheet 10 is 1.10 g / cm 3 , 1.15g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 , 1.30g / cm 3Or any value between any two of the above numerical ranges. The compacted density values in the present invention are rounded off to two decimal places when designed and recorded, but in actual production, it is still necessary to consider the slight fluctuation of the surface density value and ensure that this fluctuation is within a controllable range. By controlling the compacted density of the negative electrode plate 10, the porosity and void distribution of the negative electrode plate 10 can be controlled, so that the ion conduction ability of the battery during the charge and discharge process can be adjusted, thereby changing the rate performance of the battery. When the compacted density of the negative electrode plate 10 is greater than 1.30 g / cm 3 When the compaction density of the negative electrode sheet 10 is less than 1.10 g / cm 3 When the compaction density is too low, on the one hand, it will lead to insufficient filling of active materials in the negative electrode plate 10, thereby reducing the capacity of the battery. On the other hand, it may also lead to an increase in the voids inside the negative electrode plate 10, thereby increasing the internal resistance of the battery and affecting the rate performance of the battery.
[0053] The inventor of the present application uses the principle of interaction between the compaction density and unit surface density of the negative electrode plate 10, and controls the compaction density and double-sided surface density of the negative electrode plate 10 to control the thickness of the negative silicon-based active material on the negative electrode current collector 11, and then controls the thickness of the current collector to be between 6-8μm by selecting the negative electrode copper foil current collector, so that the thickness of the entire negative electrode plate 10 is controlled between 18μm-28μm. Such precise control of the thickness of the negative electrode plate 10 helps to reduce the voids inside the battery, thereby reducing the internal resistance of the battery and improving the battery's charge and discharge efficiency and power output capacity. At the same time, the volumetric capacity of the battery can also be optimized, thereby increasing the battery's energy density.
[0054] In one embodiment, the first coating surface 111 and the second coating surface 112 of the negative electrode plate 10 include two negative electrode coating areas, respectively, wherein the negative electrode tab 12 is disposed in the first blank area 111C between the two negative electrode coating areas of the first coating surface 111, and the negative electrode tab 12 may also be disposed in the second blank area 112C between the two negative electrode coating areas of the second coating surface 112. The first coating area 111A and the second coating area 111B included in the first coating surface 111 of the negative electrode plate 10 have the same length, and the third coating area 112A and the fourth coating area 112B included in the second coating surface 112 of the negative electrode plate 10 also have the same length.
[0055] The negative electrode plate 10 provided by the present invention is as follows Figure 1-3As shown, the negative electrode tab 12 is arranged in the middle position of the first blank area 111C between the two negative electrode coating areas of the first coating surface 111. This arrangement can make electrons flow from the first coating area 111A and the second coating area 111B on both sides of the first blank area 111C to the negative electrode tab 12 at the same time; or flow from the negative electrode tab 12 to the first coating area 111A and the second coating area 111B on both sides of the first blank area 111C, which can shorten the path of electrons in the negative electrode plate 10, thereby reducing the internal resistance of the negative electrode plate 10 and improving the rate performance of the battery.
[0056] In one embodiment of the present invention, the negative electrode tab 12 includes a first conductive sheet 121 and a first insulating sheet 122. The first conductive sheet 121 is welded to the first blank area 111C of the first coating surface 111 by a first ultrasonic weld 121A. The first insulating sheet 122 is attached to the first conductive sheet 121 and the negative electrode current collector 11 to protect the first conductive sheet 121 in the first insulating sheet 122 to prevent the positive and negative electrodes from being short-circuited due to the burrs generated by the first conductive sheet 121. Similarly, the second blank area 112C of the second coating surface 112, that is, the side away from the negative electrode tab 12, is also attached with a second insulating sheet 123 to prevent the positive and negative electrodes from being short-circuited due to the burrs generated by the first conductive sheet 121. In this embodiment, the first conductive sheet 121 in the negative electrode tab 10 is a copper-nickel tab with a width of 2-4 mm, and the first insulating sheet 122 and the second insulating sheet 123 are made of polyimide tape.
[0057] In one embodiment, the distance between the two coating areas of the first coating surface 111 of the negative electrode plate 10 is 2-8 times the width of the negative electrode tab 12. In the present invention, the width of the negative electrode tab 12 is preferably 2-4 mm, and the distance between the first coating area 111A and the second coating area 111B is preferably 4-32 mm. By reasonably setting the distance between the two coating areas, it can be ensured that the space between the negative electrode tab 12 and the two coating areas is fully utilized, which helps to increase the filling amount of active materials within a limited battery volume, thereby increasing the energy density of the battery. When the distance between the first coating area 111A and the second coating area 111B is too narrow, it may cause current concentration, increase local resistance and heat generation, and increase the risk of thermal runaway. When the distance between the first coating area 111A and the second coating area 111B is too wide, it means that the area on the negative electrode plate 10 where the active material is not coated is larger, which will result in a reduction in the filling amount of the negative electrode active material, thereby reducing the energy density of the battery.
[0058] In one embodiment, the welding area between the negative electrode tab 12 and the negative electrode plate 10 is greater than 8 mm 2 . Ensure that the welding area is larger than 8mm 2The purpose is: on the one hand, to ensure that the connection between the negative electrode tab 12 and the negative electrode sheet 10 is more stable and reliable, which helps to reduce the risk of local overheating and thermal runaway caused by poor connection; on the other hand, the increase in the welding area will reduce the contact resistance between the negative electrode tab 12 and the negative electrode sheet 10, which helps to improve the charge and discharge efficiency and rate performance of the battery.
[0059] In a second aspect, the present invention further provides a method for preparing a negative electrode sheet 10, comprising the following steps: A: The pure silicon particle material, the conductive agent and the binder are uniformly dispersed in a solvent to obtain a negative electrode coating slurry, wherein the solid content of the negative electrode slurry is 10-15wt%, and the viscosity of the negative electrode slurry is 4000-15000mPa.s -1 ; B: The negative electrode coating slurry is coated on the surface of the current collector, and the negative electrode sheet 10 is obtained after drying and rolling.
[0060] In the present invention, the conductive agent includes a one-dimensional conductive agent, a two-dimensional conductive agent and super carbon black (SP), and the one-dimensional conductive agent preferably includes one or more of single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), carbon nanofibers (CNFs), silver nanofibers and copper nanofibers; the two-dimensional conductive agent includes graphene (RGO) and / or graphene (GDY). Since super carbon black and one-dimensional conductive agents have a large specific surface area, they can increase the surface energy and improve the viscosity of the slurry after being added, but are not conducive to the dispersion of the slurry. Therefore, it is also necessary to add a two-dimensional conductive agent, such as graphene. The addition of graphene can have a lubricating effect and make the slurry easier to disperse. The present invention preferably uses single-walled carbon nanotubes, super carbon black, and graphene as negative electrode conductive agents, wherein the conductive agent can be in the form of slurry. The mass ratio of pure silicon particles to conductive agent is preferably (80-99): (0.5-20), and more preferably (85-95): (5-15).
[0061] In the present invention, the binder includes one or more of polyacrylic acid (PAA), polyacrylamide (PAM), sodium alginate (SA), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR); the addition of polyacrylic acid (PAA), polyacrylamide (PAM), sodium alginate (SA), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) can increase the viscosity of the slurry. The present invention preferably uses polyacrylic acid (PAA) and polyacrylamide (PAM) as negative electrode binders, wherein the binder can be in the form of slurry. The mass ratio of pure silicon particles to conductive agent is preferably (80-99):(0.5-20), more preferably (80-95):(5-15).
[0062] In the present invention, the total mass of pure silicon particles, conductive agent and binder is 100%, wherein the proportion of pure silicon particles is 80-99%, preferably 85-95%, such as 85%, 90%, 95%, preferably a range value with any of the above values as the upper or lower limit. The conductive agent accounts for 0.5-20%, more preferably 0.5-10%, such as 0.5%, 5%, 10%, preferably a range value with any of the above values as the upper or lower limit. The binder accounts for 0-20%, more preferably 0.5-10%, such as 0.5%, 5%, 10%, preferably a range value with any of the above values as the upper or lower limit. In the present invention, the solvent is preferably deionized water.
[0063] In the present invention, the solid content of the negative electrode slurry is controlled at 10-15wt%, and the viscosity is controlled at 4000-15000mPa.s -1 The solid content directly affects the uniformity of coating. Too high a solid content may lead to poor fluidity of the slurry, making it difficult to form a uniform coating on the electrode, thus affecting the performance of the battery. Too low a solid content will not only make coating difficult, but also cause the active material inside the electrode to easily peel off or be lost during the cycle charge and discharge process, destroying the stability of the electrode structure, thus shortening the battery life. In the present invention, the solid content is within the range of 10-15wt%, and the viscosity is controlled within the range of 4000-15000mPa·s -1 When it is within this range, the fluidity of the slurry is moderate, the slurry is easy to level and dry, which is beneficial to improving the coating efficiency and ensuring the performance of the battery.
[0064] In the present invention, pure silicon particles, a binder and a conductive agent are mixed and stirred in a mass ratio of (80-95):(5-15):(5-15) in deionized water to form a negative electrode slurry. To ensure uniformity of dispersion, the mixing time is preferably more than 3 hours. The one-dimensional conductive agent is preferably added last. This is because one-dimensional conductive agents, such as carbon nanotubes (CNTs), have a unique fibrous structure and are prone to agglomeration under the action of van der Waals forces. To avoid agglomeration, they are usually added in the final stage of the mixing process. This ensures that the conductive agent can be quickly and evenly dispersed in the electrode material after addition, thereby improving its conductive properties.
[0065] In the present invention, the current collector may be copper foil, carbon-coated copper foil or three-dimensional porous copper foil, and the thickness of the current collector is controlled to be 6 μm-8 μm, preferably 6 μm or 8 μm.
[0066] The present invention has no particular limitation on the coating method, and any coating method commonly used by those skilled in the art may be used.
[0067] In the present invention, the drying temperature is preferably 70-120°C, more preferably 80-100°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, preferably a range value with any of the above values as the upper or lower limit.
[0068] The present invention increases the total specific surface area of all particles in the slurry by using various conductive agents with higher specific surface areas, and matches them with a binder system with better thickening effect, while optimizing a better mixing sequence, thereby ensuring the fluidity of the slurry and enabling it to be mixed evenly in a shorter time.
[0069] In a third aspect, the present invention also provides a cylindrical battery 100, such as Figure 7 , which is a schematic diagram of the structure of a cylindrical battery 100 provided by the present invention. The cylindrical battery 100 provided by the present invention comprises an aluminum-plastic shell 40, a positive electrode sheet 20, a negative electrode sheet 10, a cylindrical winding core formed by a separator 30, and an electrolyte disposed in the shell. The aluminum-plastic shell 40 is sequentially wound with a separator 30, a negative electrode sheet 10, a separator 30, and a positive electrode sheet 20 to form a cylindrical winding core. The aluminum-plastic shell 40 is provided with an electrolyte, and one end outside the shell is a positive terminal, and the other end is a negative terminal.
[0070] In one embodiment, the cylindrical battery 100 provided by the present invention further includes a positive electrode sheet 20. Figure 4-6 As shown, it is a schematic diagram of the structure of the positive electrode plate 20 provided in the cylindrical battery 100 provided by the present invention. The positive electrode plate 20 includes a positive electrode current collector 21, a positive electrode tab 22 arranged on the positive electrode current collector 21, and a positive electrode active material, wherein the positive electrode active material can be selected from one of lithium manganese oxide or lithium cobalt oxide, both of which can be matched with the negative electrode plate 10 in the present invention to obtain a high-performance cylindrical battery 100. Since the electronic cigarette industry has certain requirements for high voltage and high rate of batteries, lithium iron phosphate and ternary materials have limited their application to a certain extent due to their low voltage.
[0071] The positive electrode active material in the positive electrode plate 20 provided by the present invention is lithium cobalt oxide, and the proportion of lithium cobalt oxide in the positive electrode active material is 80-100wt%. Lithium cobalt oxide has a higher first discharge specific capacity. In the positive electrode active material of the present invention, when the proportion of lithium cobalt oxide reaches 80-100wt%, it indicates that lithium cobalt oxide is the main component of the positive electrode material. This is because it is difficult to obtain 100% pure lithium cobalt oxide in actual production and application. The present invention uses high-content lithium cobalt oxide as the positive electrode active material of the electronic cigarette battery, which can store more electrical energy and provide a longer battery life. In addition, the voltage platform of lithium cobalt oxide is usually higher than many other common lithium-ion battery positive electrode materials, and the charging voltage of high-voltage lithium cobalt oxide materials can be as high as 4.3V or even 4.4V. The use of lithium cobalt oxide as the positive electrode active material to prepare an electronic cigarette lithium battery helps the electronic cigarette to provide a more stable voltage output when working, ensuring the normal operation of the electronic cigarette.
[0072] In one embodiment, the average particle size of the positive electrode active material lithium cobalt oxide provided by the present invention is 4.5-6.0 μm. For example, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, preferably any value between any two of the above numerical ranges. The present invention uses lithium cobalt oxide particles with small particle size, which is beneficial to Li + The embedding and de-embedding of ions and electrons shortens the transmission path of ions and electrons inside the material, reduces the internal resistance, and further improves the performance of the battery.
[0073] In the positive electrode sheet 20 provided by the present invention, Figure 6The positive electrode current collector 21 shown includes a third coating surface 211 and a fourth coating surface 212 arranged along its own thickness direction Z. The third coating surface 211 includes a fifth coating area 211A and a sixth coating area 211B, and the fourth coating surface 212 includes a seventh coating area 212A and an eighth coating area 212B. The positive electrode active material is arranged on the fifth coating area 211A and the sixth coating area 211B of the third coating surface 211, and on the seventh coating area 212A and the eighth coating area 212B of the fourth coating surface 212, that is, the positive electrode active material is respectively located on two opposite surfaces of the positive electrode current collector 21. The fifth coating area 211A and the sixth coating area 211B included in the third coating surface 211 of the positive electrode plate 20 have the same length. The coating area seventh coating area 212A and the eighth coating area 212B included in the fourth coating surface 212 of the positive electrode plate 20 also have the same length. The third coating surface 211 is provided with a third side 213, and there is no negative electrode silicon-based active material in the third side 213. The third blank area 211C and the third side 213 without positive electrode active material are the surface of the positive electrode current collector 21 itself. The fourth coating surface 212 is provided with a fourth side 214, and there is no negative electrode silicon-based active material in the fourth side 214. The positive electrode tab 22 is arranged in the third blank area 211C between the two positive electrode coating areas of the third coating surface 211, or in the fourth blank area 212C between the two positive electrode coating areas of the fourth coating surface 212.
[0074] The positive electrode plate 20 provided by the present invention is as follows Figure 4-6 As shown, the positive electrode tab 22 is arranged in the middle position of the third blank area 211C between the two positive electrode coating areas of the third coating surface 211. This arrangement can make electrons flow from the fifth coating area 211A and the sixth coating area 211B on both sides of the third blank area 211C to the positive electrode tab 22 at the same time; or flow from the positive electrode tab 22 to the fifth coating area 211A and the sixth coating area 211B on both sides of the third blank area 211C, which can shorten the path of electrons in the positive electrode sheet 20, thereby reducing the internal resistance of the positive electrode sheet 20, which helps to improve the charge and discharge efficiency of the battery and improve the battery rate performance.
[0075] In one embodiment of the present invention, the positive electrode tab 22 includes a second conductive sheet 221 and a third insulating sheet 222. The second conductive sheet 221 is welded to the third blank area 211C of the third coating surface 211 by a second ultrasonic weld 221A. The third insulating sheet 222 is attached to the second conductive sheet 221 and the positive electrode current collector 21 to protect the second conductive sheet 221 in the third insulating sheet 222 to prevent the positive and negative electrodes from being short-circuited due to the burrs generated by the second conductive sheet 221. Similarly, a fourth insulating sheet 223 is also attached to the fourth blank area 212C of the fourth coating surface 212, that is, the side away from the positive electrode tab 22, to prevent the positive and negative electrodes from being short-circuited due to the burrs generated by the second conductive sheet 221.
[0076] The width of the positive electrode tab 22 of the positive electrode sheet 20 provided by the present invention is the same as the width of the negative electrode tab 12 of the negative electrode sheet 10. That is, the width of the second conductive sheet 221 in the positive electrode sheet 20 is the same as the width of the first conductive sheet 121 in the negative electrode sheet 10. In this embodiment, the second conductive sheet 221 in the positive electrode sheet 20 is an aluminum tab with a width of 2-4 mm, and the third insulating sheet 222 and the fourth insulating sheet 223 are made of polyimide tape.
[0077] In one embodiment of the present invention, the length of the negative electrode sheet 10 is greater than the length of the positive electrode sheet 20, and the negative electrode sheet 10 covers the positive electrode sheet 20. Specifically, the length of the third side 213 or the fourth side 214 of the positive electrode sheet 20 is greater than the first side 113 or the second side 114 of the negative electrode sheet 10, and the length of the third blank area 211C or the fourth blank area 212C of the positive electrode sheet 20 is greater than the length of the first blank area 111C or the second blank area 112C of the negative electrode sheet 10, so that the negative electrode active material can completely cover the positive electrode active material to avoid lithium deposition of the negative electrode sheet 10 and / or the positive electrode sheet 20. In the cylindrical winding process of the present invention, the separator 30 is rolled in first, and the positive electrode sheet 20 is rolled in after the negative electrode sheet 10 is rolled in 1.5 turns, so that the negative electrode sheet 10 covers the positive electrode sheet 20, and the outer ring separator 30 covers the negative electrode sheet 10.
[0078] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 745-750mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 745mm, 746mm, 747mm, 748mm, 749mm, 750mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 20-25mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 20mm, 21mm, 22mm, 23mm, 24mm, 25mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800-805mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800mm, 801mm, 802mm, 803mm, 804mm, 805mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 20-25mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 20mm, 21mm, 22mm, 23mm, 24mm, 25mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 13300 model battery, wherein the shell size of the cylindrical battery 100 corresponding to 13300 is 13mm in diameter and 300mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 580-700mAh at a discharge rate of 0.2C.
[0079] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 745-750mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 745mm, 746mm, 747mm, 748mm, 749mm, 750mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 25-30mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 25mm, 26mm, 27mm, 28mm, 29mm, 30mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800-805mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800mm, 801mm, 802mm, 803mm, 804mm, 805mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 25-30mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 25mm, 26mm, 27mm, 28mm, 29mm, 30mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 13350 size battery, wherein the shell size of the cylindrical battery 100 corresponding to 13350 is 13mm in diameter and 350mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 710-810mAh at a discharge rate of 0.2C.
[0080] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 745-750mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 745mm, 746mm, 747mm, 748mm, 749mm, 750mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 30-35mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 30mm, 31mm, 32mm, 33mm, 34mm, 35mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800-805mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 800mm, 801mm, 802mm, 803mm, 804mm, 805mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 30-35mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 30mm, 31mm, 32mm, 33mm, 34mm, 35mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 13400 model battery, wherein the shell size of the cylindrical battery 100 corresponding to 13400 is 13mm in diameter and 400mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 820-920mAh at a discharge rate of 0.2C.
[0081] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 1300-1320 mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 1300 mm, 1305 mm, 1310 mm, 1315 mm, 1320 mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 25-35 mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 25 mm, 27 mm, 29 mm, 31 mm, 33 mm, 35 mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360-1380 mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360 mm, 1365 mm, 1370 mm, 1375 mm, 1380 mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 25-35 mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 25 mm, 27 mm, 29 mm, 31 mm, 33 mm, 35 mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 18350 model battery, wherein the shell size of the cylindrical battery 100 corresponding to 18350 is 18mm in diameter and 350mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 1000-1600mAh at a discharge rate of 0.2C.
[0082] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 1300-1320 mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 1300 mm, 1305 mm, 1310 mm, 1315 mm, 1320 mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 40-45 mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 40 mm, 41 mm, 42 mm, 43 mm, 44 mm, 45 mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360-1380 mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360 mm, 1365 mm, 1370 mm, 1375 mm, 1380 mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 40-45 mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 40 mm, 41 mm, 42 mm, 43 mm, 44 mm, 45 mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 18500 model battery, wherein the shell size of the cylindrical battery 100 corresponding to 18500 is 18mm in diameter and 500mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 2100-2400mAh at a discharge rate of 0.2C.
[0083] In one embodiment, the length of the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention is 1300-1320 mm; for example, the length of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 1300 mm, 1305 mm, 1310 mm, 1315 mm, 1320 mm, or any value between any two of the above numerical ranges. The width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 50-55 mm; for example, the width of the positive electrode sheet 20 of the cylindrical battery 100 provided by the present invention is 50 mm, 51 mm, 52 mm, 53 mm, 54 mm, 55 mm, or any value between any two of the above numerical ranges. The length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360-1380 mm; for example, the length of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 1360 mm, 1365 mm, 1370 mm, 1375 mm, 1380 mm, or any value between any two of the above numerical ranges. The width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 50-55 mm; for example, the width of the negative electrode sheet 10 of the cylindrical battery 100 provided by the present invention is 50 mm, 51 mm, 52 mm, 53 mm, 54 mm, 55 mm, or any value between any two of the above numerical ranges. The capacity ratio (N / P ratio) of the positive electrode sheet 20 and the negative electrode sheet 10 in the cylindrical battery 100 provided by the present invention is 1.2-1.4. The lengths of the negative electrode sheet 10 and the positive electrode sheet 20 in the cylindrical battery 100 provided by the present invention meet the shell size of the 18600 battery, wherein the shell size of the cylindrical battery 100 corresponding to 18600 is 18 mm in diameter and 600 mm in height. The cylindrical battery 100 provided by the present invention has a battery capacity of 2500-2900 mAh at a discharge rate of 0.2C.
[0084] In addition, the present invention also provides an electronic cigarette, including the above-mentioned cylindrical battery 100. The cylindrical battery 100 has a high energy density. The use of the cylindrical battery 100 can extend the use time of the electronic cigarette and reduce frequent charging. The cylindrical battery 100 in the present invention has a high voltage platform, which helps to ensure that the electronic cigarette produces a consistent amount of smoke and taste during use, improves the user experience, and helps the electronic cigarette product have excellent performance and improves market competitiveness.
[0085] The present invention is further described in detail below in conjunction with embodiments and comparative examples: Below, the embodiment of the application is described. The facts described below are exemplary and are only used to explain the application, and cannot be construed as limiting the application. In the embodiment, no specific technology or conditions are indicated, and the technology or conditions described in the literature in this area or the product instructions are carried out. The reagents used or the unindicated manufacturers are all conventional products that can be obtained commercially.
[0086] 1. Cylindrical battery 100 Example 1
[0087] (1) Preparation of negative electrode sheet 10: Micron pure silicon particles were used as negative electrode silicon-based active materials, and were mixed and stirred evenly with binder PAA, binder PAM, conductive agent CNT, conductive agent SP, and conductive agent RGO in a mass ratio of 91:0.8:1.7:1:2:2 in deionized water to prepare negative electrode slurry. 2 The surface density is double-sidedly coated on the surface of a copper foil with a thickness of 6μm and a length of 803mm. The coated length is 784mm, the blank length at one end is 7mm, and a 12mm blank area is left in the middle position of the length direction of the front side of the negative electrode plate 10. It is cold-pressed and cut into a plate with a width of 24mm, a thickness of 21μm, and a length of 803mm. After the 12mm blank area in the middle position of the length direction of the front side of the negative electrode plate 10 is welded to the pole ear, a negative electrode plate 10 with a negative electrode silicon-based active material attached to the surface is obtained, and the gram capacity of the negative electrode silicon-based active material in the negative electrode plate 10 is 3600mAh / g.
[0088] (2) Preparation of positive electrode sheet 20: Lithium cobalt oxide (LCO) was used as the positive electrode active material. It was mixed with binder polytetrafluoroethylene (PVDF) and conductive agent SP and conductive agent MWCNT in N-methylpyrrolidone (NMP) at a mass ratio of 96:1.14:1.5:1.09 to prepare a positive electrode slurry. 2 The positive electrode slurry is coated on both sides of an aluminum foil with a thickness of 12μm and a length of 748mm, with a blank length of 10mm on one end, and a 48mm blank area is left in the middle of the length direction of the front side of the positive electrode sheet 20. It is cold-pressed and cut into a positive electrode sheet 20 with a width of 23±1mm, a thickness of 81μm, and a length of 748mm. The positive electrode ear 22 is welded in the blank area in the middle of the length direction of the front side of the positive electrode sheet 20 to obtain a positive electrode sheet 20 with positive active material attached to the surface.
[0089] (3) Preparation of diaphragm 30 The selected diaphragm 30 has a thickness of 16 μm, a material of ceramic / polyethylene (PE) / ceramic three-layer isolation membrane, a length of 1850 mm, and a width of 27 mm.
[0090] (4) Preparation of electrolyte In a glove box filled with argon (water <10ppm, oxygen <10ppm), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (EC), and fluoroethylene carbonate (FEC) were mixed at a mass ratio of DEC:PC:EC:FEC=45:21:11:3 to obtain an organic solvent. Then, lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare a solution with a lithium salt concentration of 1.0 mol / L, and then vinyl sulfate (DTD), adiponitrile (ADN), and 1,3-propylene sultone (PST) were added and mixed evenly to obtain an electrolyte.
[0091] (5) Assembly of cylindrical battery 100 (a): placing the prepared negative electrode sheet 10 and positive electrode sheet 20 into a vacuum oven to bake and remove water; (b): The baked negative electrode sheet 10 and the positive electrode sheet 20 and the separator 30 are stacked in the order of "separator 30 / negative electrode sheet 10 / separator 30 / positive electrode sheet 20" and then wound into a cylindrical winding core. When winding, the side without side edges of the negative electrode sheet 10 is wound first, and at the same time, it is ensured that the coated surface of the negative electrode sheet 10 completely covers the coated surface of the positive electrode sheet 20; (c): Punching the aluminum-plastic film according to the ratio of the diameter of the cylindrical core to the inner diameter of the aluminum-plastic film pit depth of 0.98, and inserting the cylindrical core into the pit of the aluminum-plastic shell 40; (d): hot pressing the aluminum-plastic shell 40 on both sides of the positive and negative tabs for 3-6 seconds at 180-290°C and 0.4-0.6MPa, so that the tab seal strength is greater than 30N and the aluminum-plastic shell 40 seal strength is greater than 100N; (e) Baking the semi-finished battery cell, injecting 1.67g of electrolyte according to the injection process, sealing and soaking, and then charging and forming; (f): After the formation, the battery cell is trimmed and sealed again at a vacuum degree of -90KPa, a sealing temperature of 200-220℃, and a sealing pressure of 0.4-0.5MPa, so that the packaging strength is >100N; (g): The battery cell after the second sealing is folded, the pole ear is folded, and the glue is applied according to the packaging process to obtain a finished product 13300 model battery cell.
[0092] Embodiment 2-5: Examples 2-5 are used to illustrate other 13300-model cylindrical batteries 100 of the present invention, including most of the operations in Example 1, with the difference being that: the negative electrode active materials of the cylindrical batteries 100 in Examples 2-4 are different. When silicon-carbon and graphite materials are used as negative electrode silicon-based active materials, the mass percentage of silicon element in the negative electrode silicon-based active material is different due to the different contents of silicon-carbon or graphite in the negative electrode silicon-based active material. The specific parameters shall be subject to the data shown in Table 1 corresponding to each embodiment.
[0093] Comparative Examples 1-3: The comparative examples 1-3 are used to compare and illustrate the cylindrical battery 100 of model 13300, including most of the operations in Example 1, except that: the selection of materials in the negative electrode silicon-based active material in the comparative examples 1-3 is different, so that the mass percentage content of silicon element in the negative electrode silicon-based active material is different. The specific parameters are subject to the data shown in Table 1 corresponding to each embodiment.
[0094] Embodiment 6-10: Examples 6-10 are used to illustrate the 13400-size cylindrical battery 100 of the present invention, including most of the operations in Example 1, except that the average particle sizes of the negative electrode active materials in Examples 6-10 are different, and the specific parameters are subject to the data shown in Table 1 corresponding to each example.
[0095] Embodiment 11-16: Examples 11-16 are used to illustrate the 13350-model cylindrical battery 100 of the present invention, including most of the operations in Example 1, except that: the coating surface density of the negative electrode plate 10 in Examples 11-16 is different, resulting in different layer thicknesses of the negative electrode plate 10. The specific parameters are subject to the data shown in Table 1 corresponding to each embodiment.
[0096] Embodiment 17-23: Examples 17-23 are used to illustrate the 18600-type cylindrical battery 100 of the present invention, including most of the operations in Example 1, except that: the compaction density of the negative electrode silicon-based active material in Examples 17-23 is different, resulting in different thicknesses of the negative electrode plate 10. The specific parameters are subject to the data shown in Table 1 corresponding to each embodiment.
[0097] Embodiment 24-25: Examples 24-25 are used to illustrate the 18350-type cylindrical battery 100 of the present invention, including most of the operations in Example 1, except that the positive electrode active materials in Examples 24-25 are different, and the specific parameters are subject to the data shown in Table 1 corresponding to each example.
[0098] Embodiment 26-30: Examples 26-30 are used to illustrate the 18500-size cylindrical battery 100 of the present invention, including most of the operations in Example 1, except that the average particle size of the positive electrode active material in Examples 26-30 is different, and the specific parameters are subject to the data shown in Table 1 corresponding to each example.
[0099] Table 1 Parameters of Examples 1-30 and Comparative Examples 1-3
[0100] 2. Performance test of the cylindrical battery 100 prepared in the above manner (1) 0.2C discharge test method and battery capacity test At an ambient temperature of 25°C, charge the battery to 4.35V at a rate of 0.2C, then charge at a constant voltage until the battery is fully charged. After standing for 30 minutes, discharge the battery to 2.5V at a rate of 0.2C, record the discharge temperature rise and capacity, and record the discharge capacity as the nominal capacity of the battery cell.
[0101] (2) 3A discharge test method At an ambient temperature of 25°C, charge the battery to 4.35V at a rate of 0.2C, then charge it at a constant voltage until the battery is fully charged. After standing for 30 minutes, discharge it to 2.5V at a current of 3A, and record the discharge temperature rise and capacity.
[0102] (3) 6A discharge test method At an ambient temperature of 25°C, charge the battery to 4.35V at a rate of 0.2C, then charge it at a constant voltage until the battery is fully charged. After standing for 30 minutes, discharge it to 2.5V at a current of 6A, and record the discharge temperature rise and capacity.
[0103] (4) 8A discharge test method At an ambient temperature of 25°C, charge the battery to 4.35V at a rate of 0.2C, then charge it at a constant voltage until the battery is fully charged. After standing for 30 minutes, discharge it to 2.5V at a current of 8A, and record the discharge temperature rise and capacity.
[0104] III. Analysis of test results of various embodiments and comparative examples According to the above method, cylindrical batteries 100 of various embodiments and comparative examples were prepared respectively, and various performance parameters were measured. The results are shown in Table 2 below.
[0105] Table 2 Test results of Examples 1-30 and Comparative Examples 1-3
[0106] As can be seen from Example 1, for a 13300 cylindrical battery 100, when the pure silicon content in the negative electrode silicon-based active material is 100%, the negative electrode active material is 3.5 μm pure silicon particles, and the surface density of the negative electrode plate 10 is 1.9 mg / cm 2 , compacted density is 1.27g / cm 3 , the thickness of the active material coating on the negative electrode sheet 10 is 15μm, that is, the sum of the thickness of the first coating surface 111 and the second coating surface 112 of the upper and lower surfaces of the negative electrode current collector 11 is controlled between 12μm and 20μm. At the same time, when the positive electrode active material is 5.0μm lithium cobalt oxide, under these parameters, the capacity of the battery is 650mAh, that is, at a discharge rate of 0.2C, the capacity of the 13300 cylindrical battery 100 is 580-700mAh. The capacity retention rate of the battery at a discharge rate of 3A is 98%, and the temperature rise is 16.9℃; at discharge rates of 6A and 8A, the capacity retention rate of the battery is reduced to below 90%, and the temperature rise is also significantly increased. This is mainly because as the discharge rate increases, the discharge current increases, the heat generated increases, and the time for the battery to dissipate heat with the external environment is reduced. The heat generated inside the battery is difficult to dissipate quickly, resulting in an increase in the battery temperature. At the same time, the electrochemical reaction rate inside the battery is accelerated accordingly, and the polarization effect inside the battery is enhanced, and the polarization effect will hinder the migration of lithium ions, resulting in a decrease in the capacity of the battery. Comparing the data of cylindrical batteries 100 of different models in Table 2, they all conform to the above change rules.
[0107] It can be seen from Examples 1-5 and Comparative Examples 1-3 that as the proportion of pure silicon in the negative electrode silicon-based active material gradually decreases, the capacity of the 13300 model cylindrical battery 100 shows a gradually decreasing trend. This is mainly because pure silicon has an extremely high theoretical specific capacity, which is much higher than traditional graphite. The decrease in the proportion of pure silicon in silicon-based materials will cause the specific capacity of the overall negative electrode active material to decrease, thereby causing the capacity of the battery to gradually decrease. It can be seen from Example 2 that when the proportion of pure silicon is 95%, the capacity of the battery is 630mAh, which is slightly lower than that of Example 1, but at the discharge rates of 6A and 8A, the capacity retention rate of the battery is relatively high. This is mainly because the negative electrode active material contains a small amount of graphite, and the graphite rate performance is better than that of pure silicon particles. The combination of the two active materials is beneficial to improving the rate performance of the battery and increasing the capacity retention rate of the battery. In combination with Examples 2-5, it can be seen that a small amount of graphite is compounded with pure silicon particles or silicon-carbon materials as the negative electrode active material of the battery, and the battery has a higher energy density and excellent rate performance. It can be seen from Comparative Examples 1-3 that when the proportion of graphite or silicon-carbon material in the negative electrode active material is high, although the rate performance of the battery is improved to a certain extent, since the gram capacity of graphite and silicon-carbon materials is lower than that of pure silicon, this will affect the energy density of the entire negative electrode material to a certain extent, so the battery capacity is less than 600mAh.
[0108] It can be seen from Examples 6-10 that for the 13400 model cylindrical battery 100, the main thing is to adjust the average particle size of the pure silicon particles of the negative electrode active material. It can be seen from the table that when the average particle size of the pure silicon particles is between 3.0-6.5μm, the capacity of the 13400 model cylindrical battery 100 in Examples 6-8 is above 820mAh. However, as the average particle size increases, the battery capacity gradually decreases. This is because when the particle size of the negative electrode material increases, the effective surface area decreases, and the contact area between the electrode and the electrolyte also decreases, resulting in a decrease in the battery capacity. Under high-rate discharge conditions, the capacity retention rate of the battery gradually decreases with the increase of the average particle size of the pure silicon particles, but the temperature rise inside the battery gradually increases. This is mainly because large-size pure silicon particles are more likely to produce mechanical stress and thermal effects due to large volume changes during the lithium insertion and delithiation process. On the one hand, this will accelerate the accumulation of heat inside the battery and increase the temperature of the battery. On the other hand, it may also cause the particles to break and pulverize. The electrical contact between the pulverized silicon particles and the current collector becomes poor, resulting in a decrease in the utilization rate of the active material, thereby reducing the capacity retention rate of the battery. Therefore, selecting pure silicon particles with an average particle size of 3.0-6.0μm helps to maintain a more stable performance of the battery.
[0109] It can be seen from Examples 11-16 that for the 13350 cylindrical battery 100, the main thing is to adjust the surface density of the negative electrode sheet 10. As can be seen from Table 1, when the surface density of the negative electrode sheet 10 is between 1.6 and 2.4 mg / cm 2 When adjusted within the range, the capacity of the 13350 cylindrical battery 100 is above 710 mAh. As the surface density of the negative electrode sheet 10 increases, the coating thickness of the negative electrode sheet 10 gradually increases, but is controlled between 12 μm and 20 μm. This is mainly because as the coating thickness of the negative electrode sheet 10 increases, more active materials are available, which can increase the lithium storage capacity of the battery to a certain extent, thereby facilitating the improvement of the battery capacity. As can be seen from Example 15, when the surface density of the negative electrode sheet 10 is 1.6 mg / cm 2 When the surface density is low, it means that there is less active material per unit area, and the number of lithium ions that can be stored and released during the charge and discharge process is limited, so the battery capacity is the lowest. 2 When the surface density is high, it means that more negative electrode active materials are loaded on the same area, but the increase in surface density will also increase the thickness of the negative electrode plate 10 and increase the internal resistance of the battery, thereby affecting the rate performance of the battery and limiting the improvement of the battery capacity to a certain extent.
[0110] It can be seen from Examples 17-23 that for the 18600 cylindrical battery 100, the main thing is to adjust the compaction density of the negative electrode sheet 10. As can be seen from the table, when the compaction density of the negative electrode sheet 10 is between 1.10 and 1.30 g / cm 3 When adjusted within the range, the battery capacity of the 18600 cylindrical battery 100 is above 2500mAh. It can be seen from Examples 19-21 that as the compaction density of the negative electrode sheet 10 increases, the coating thickness of the negative electrode sheet 10 gradually decreases, but is controlled between 12μm-20μm. As the thickness of the negative electrode sheet 10 decreases, under the condition that the battery volume remains unchanged, the length of the negative electrode sheet 10 increases, so the capacity of the battery gradually increases. Examples 17-19 and Examples 21-23 are respectively 1.10g / cm 3 and 1.30g / cm 3 The test results of the battery corresponding to different thicknesses of the negative electrode sheet 10 under the compaction density of. As the thickness of the negative electrode sheet 10 decreases, the capacity of the battery cell shows a downward trend, which is mainly due to the influence of the surface density adjustment.
[0111] It can be seen from Examples 24-25 that for the 18350 cylindrical battery 100, the main adjustment is the positive electrode active material. Due to the special requirements of the electronic cigarette industry for high voltage and high rate of batteries, for example, lithium iron phosphate and ternary materials are limited to a certain extent in large-scale application because of their lower voltage. From the test results of Examples 24-25, it can be seen that when pure silicon is used as the negative electrode and the positive electrode is made of lithium cobalt oxide and lithium manganese oxide materials, the battery capacity is between 1000-1450mAh. Since lithium manganese oxide has a lower theoretical capacity than lithium cobalt oxide, the corresponding battery capacity is also lower. Lithium cobalt oxide has excellent rate performance, and its capacity retention rate at high rate discharge is high. Lithium manganese oxide performs poorly under high rate discharge conditions. This is mainly because the battery temperature rise is high under high rate discharge conditions, causing manganese ions to dissolve, which seriously affects the rate performance of the battery.
[0112] As can be seen from Examples 26-30, for the 18500 cylindrical battery 100, the main adjustment is the average particle size of the positive electrode active material. As can be seen from the table, when the average particle size of the positive electrode material lithium cobalt oxide is between 4.5-6.5 μm, the capacity of the 18500 cylindrical battery 100 in Examples 26-30 is 2250 mAh. This is mainly because the average particle size of the general high-voltage lithium cobalt oxide may reach the range of 16 μm-20 μm, and the average particle size of the lithium cobalt oxide used in the present invention is between 4.5-6.5 μm. The volume change of the positive electrode material with a smaller particle size during the charge and discharge process is relatively small, which helps to maintain the stability of the battery performance, and therefore has little effect on the battery capacity. As can be seen from Example 28, when the particle size of the positive electrode material lithium cobalt oxide is greater than 6.0 μm, the rate performance of the battery gradually decreases. This is because as the particle size of the positive electrode material increases, the diffusion path of lithium ions in the material will become longer, and the diffusion resistance will also increase accordingly. This will cause the transfer rate of lithium ions to slow down during the charge and discharge process, thus affecting the rate performance of the battery. Therefore, choosing lithium cobalt oxide particles with an average particle size of 4.5-6.0μm will help keep the performance of the battery more stable.
[0113] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode plate, characterized in that: It includes a negative electrode current collector, a negative electrode tab arranged on the negative electrode current collector, and a negative electrode silicon-based active material; The negative electrode silicon-based active material comprises pure silicon particles, and the mass percentage of the pure silicon particles in the negative electrode silicon-based active material is 65-100%; The negative electrode silicon-based active material forms a first coating surface and a second coating surface on the upper and lower surfaces of the negative electrode current collector, respectively. The sum of the thicknesses of the first coating surface and the second coating surface is 12 μm-20 μm.
2. A negative electrode sheet according to claim 1, characterized in that: The gram capacity of the pure silicon particles is ≥3200 mAh / g.
3. A negative electrode sheet as claimed in claim 2, characterized in that: The average particle size of the pure silicon particles is 3.0-6.0 μm.
4. A negative electrode sheet according to claim 1, characterized in that: The double-sided surface density of the negative electrode plate is 1.6-2.4 mg / cm 2 .
5. A negative electrode sheet as claimed in claim 4, characterized in that: The compaction density of the negative electrode plate is 1.1-1.3 g / cm 3 .
6. A negative electrode sheet as claimed in claim 5, characterized in that: The thickness of the negative electrode plate is 18 μm-28 μm.
7. A negative electrode sheet according to claim 1, characterized in that: The first coated surface and the second coated surface respectively include two negative electrode coating areas, and the negative electrode tab is welded in a first blank area between the two negative electrode coating areas of the first coated surface, or the negative electrode tab is welded in a second blank area between the two negative electrode coating areas of the second coated surface.
8. A negative electrode sheet as claimed in claim 7, characterized in that: The distance between the two coating areas is 2-8 times the width of the negative electrode tab.
9. A negative electrode sheet as claimed in claim 7, characterized in that: The welding area between the negative electrode tab and the negative electrode sheet is greater than 8 mm 2 .
10. A method for preparing a negative electrode sheet according to any one of claims 1 to 9, characterized in that: The following steps are involved: A. Evenly disperse pure silicon particle material, conductive agent and binder in a solvent to obtain negative electrode coating slurry, wherein the solid content of the negative electrode slurry is 10-15wt%, and the viscosity of the negative electrode slurry is 4000-15000mPa.s -1 ; B. The negative electrode coating slurry is coated on the surface of the current collector, and the negative electrode sheet is obtained after drying and rolling.
11. A cylindrical battery, characterized in that: The invention comprises an aluminum-plastic shell, an electrolyte placed in the shell and a cylindrical winding core, wherein the cylindrical winding core comprises a positive electrode sheet, a separator and a negative electrode sheet as claimed in any one of claims 1 to 9.
12. A cylindrical battery as claimed in claim 11, characterized in that: The positive electrode plate comprises a positive electrode current collector, a positive electrode tab disposed on the positive electrode current collector, and a positive electrode active material, wherein the positive electrode active material is one of lithium manganese oxide or lithium cobalt oxide.
13. A cylindrical battery as claimed in claim 12, characterized in that: The proportion of lithium cobalt oxide in the positive electrode active material is 80-100wt%.
14. A cylindrical battery as claimed in claim 13, characterized in that: The average particle size of the lithium cobalt oxide is 4.5-6.0 μm.
15. A cylindrical battery according to any one of claims 11 to 14, characterized in that: The positive electrode active material forms a third coating surface and a fourth coating surface on the upper and lower surfaces of the positive electrode current collector, respectively; the third coating surface and the fourth coating surface respectively include two positive electrode coating areas, and the positive electrode tab is welded in a third blank area between the two positive electrode coating areas of the third coating surface, or the positive electrode tab is welded in a fourth blank area between the two positive electrode coating areas of the fourth coating surface.
16. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 745-750mm and the width is 20-25mm; the length of the negative electrode plate is 800-805mm and the width is 20-25mm; the cylindrical battery has a battery capacity of 580-700mAh at a discharge rate of 0.2C.
17. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 745-750mm and the width is 25-30mm; the length of the negative electrode plate is 800-805mm and the width is 25-30mm; the cylindrical battery has a battery capacity of 710-810mAh at a discharge rate of 0.2C.
18. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 745-750mm and the width is 30-35mm; the length of the negative electrode plate is 800-805mm and the width is 30-35mm; the cylindrical battery has a battery capacity of 820-920mAh at a discharge rate of 0.2C.
19. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 1300-1320mm and the width is 25-35mm; the length of the negative electrode plate is 1360-1380mm and the width is 25-35mm; the cylindrical battery has a battery capacity of 1000-1600mAh at a discharge rate of 0.2C.
20. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 1300-1320mm and the width is 40-45mm; the length of the negative electrode plate is 1360-1380mm and the width is 40-45mm; the cylindrical battery has a battery capacity of 2100-2400mAh at a discharge rate of 0.2C.
21. A cylindrical battery as claimed in claim 15, characterized in that: The length of the positive electrode plate is 1300-1320mm and the width is 50-55mm; the length of the negative electrode plate is 1360-1380mm and the width is 50-55mm; the cylindrical battery has a battery capacity of 2500-2900mAh at a discharge rate of 0.2C.
22. An electronic cigarette, characterized in that: A cylindrical battery comprising a cylindrical battery as described in any one of claims 11 to 21.
Citation Information
Patent Citations
A method for preparing a lithium-ion battery for electronic cigarettes
CN111342005B
Preparation method of super-large-diameter cylindrical electronic cigarette battery
CN118738292A
Negative pole piece of lithium ion battery, and lithium ion battery using the negative pole piece
CN109585781A
High-capacity-density lithium ion battery negative electrode
CN111384370A
Silicon-based negative electrode plate of high-energy-density lithium ion battery and preparation method of silicon-based negative electrode plate
CN115732633A
Cited By
Negative electrode sheet and preparation method therefor, cylindrical battery, and electronic cigarette
WO2026148790A1